Theories of truth as assessment criteria in judgment and decision making - Philip T. Dunwoody; Philip T. Dunwoody; Robin Hogarth (Judgment and Decision Making, 2009)
Hammond (1996) argued that much of the research in the field of judgment and decision making (JDM) can be categorized as focused on either coherence or correspondence (C&C) and that, in order to understand the findings of the field, one needs to understand the differences between these two criteria. Hammond’s claim is that conclusions about the competence of judgments and decisions will depend upon the selection of coherence or correspondence as the criterion (Hammond, 2008). First, I provide an overview of the terms coherence and correspondence (C&C) as philosophical theories of truth and relate them to the field of JDM. Second, I provide an example of Hammond’s claim by examining literature on base rate neglect. Third, I examine Hammond’s claim as it applies to the broader field of JDM. Fourth, I critique Hammond’s claim and suggest that refinements to the C&C distinction are needed. Specifically, the C&C distinction 1) is more accurately applied to criteria than to researchers, 2) should be refined to include two important types of coherence (inter and intrapersonal coherence) and 3) neglects the third philosophical theory of truth, pragmatism. Pragmatism, as a class of criteria in JDM, is defined as goal attainment. In order to provide the most complete assessment of human judgment possible, and understand different findings in the field of JDM, all three criteria should be considered.